Indoor Monitoring System For Well-being - Kočka, Jakub; Arm, Jakub (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2023)
The work address the indoor air quality monitoringenabling to monitor the well-being and comfort of occupants.A monitoring system is able to measure room temperature,humidity, barometric pressure, CO2, luminosity, and dust pollutionusing chip sensors. The measurement devices are connectedwirelessly via ZigBee 3.0 technology enabling mesh networktopology and the measured data is collected into a database.The data will be then processed and presented using a cloudapplication enabling advanced control and alarm management,when a value exceeds the health limits. The measurement systemcomprises of measurement devices and a gateway. The measurementdevice is designed as a sandwich architecture comprisingsensor and communication module. The created sensor moduleis interfaced with Adafruit Feather interface in order to useany available Adafruit SoC kit as the communication module.The conducted results also suggest that ESP32-H2, which isnow in pre-production phase, operates as ZigBee 3.0 SoC inan embedded device.
Keywords: Indoor air quality; ZigBee 3.0; ESP32-H2,NRF52840; Smart Home; IoT